Epidemiology of Escherichia coli as a Critical Pathogen of Bloodstream Infection Patients in Tertiary Referral Hospital - Endraswari, Pepy; Mertaniasih, Ni Made; Setiawan, Firman; Paramita, Ayu Lidya (Indonesian Journal of Tropical and Infectious Disease, 2022)
Bloodstream infections (BSI), caused primarily by multidrug-resistant Escherichia coli, are a significant cause of morbidity and mortality worldwide. This study aims to evaluate the epidemiology of E. coli as a critical pathogen in patients with bloodstream infections in a tertiary referral hospital. This is a retrospective study using a  descriptive observational research design. This study used a medical record instrument for bloodstream patients in Dr. Soetomo Hospital's inpatient ward with Gram-negative bacteria results of blood cultures in the Clinical Microbiology Laboratory from April 2021 to September 2021. The observed variables include; antimicrobial sensitivity, patient clinical characteristics, demographic data, clinical diagnosis, and clinical outcome. In 6 months, 276 Gram-negative bloodstream infection patients were treated at Dr. Soetomo Hospital. The proportion of E. coli was 17 %.  The main characteristics of patients were over 60 years old (28%), and 54% were female. 63% of E. coli were ESBL, and 9% were carbapenem-resistant microorganisms. High antimicrobial resistance was found in quinolones (100%), ampicillin (93%), piperacillin (74%), tetracycline (72%), ceftriaxone (66%), cefotaxime (65%), ceftazidime (60%), cefazolin (65%), and trimethoprim-sulfamethoxazole (65%). The most common potential determinant profile discovered was linked to immunocompromised status due to malignancy.  The high number of antimicrobial-resistant bacteria showed the importance of strict infection control and updated epidemiology data as a guide for empirical antimicrobial therapy.